Making Sense of Recession: Toward an Interpretive Theory of Economic Action - Abolafia, Mitchell (Journal of Economic Sociology, 2010)
By reading the text we are taken to the meeting of Federal Reserve System Committee of the USA which takes the key decisions on money policy. We find out that the development of money policy is far from the mechanic process of aggregating the individual preferences of those who are responsible for taking decisions. We speak about very complicated process of bargaining of various interests and positions. From the beginning the participants of this process are aimed at the consensus and legitimization of their actions in the eyes of public opinion.